Climate projections over the Antarctic Peninsula region to the end of the 21st century. Part 1: cold temperature indices - Chyhareva, A.; Krakovska, S.; Pishniak, D. (Український антарктичний журнал, 2019)
Objective. This paper deals with an estimation of the climate change at the Antarctic Peninsula region. During last decades, the most significant warming is observed in Polar regions, particularly in the Antarctic Peninsula region, where the Ukrainian Antarctic Akademik Vernadsky station is located. Therefore, the providing of the complex estimation of climate change trend is an important task for the region. These changes are taking place nowadays and will happen in the future. So, the main objective of the study is to estimate changes of climate characteristics in the Antarctic Peninsula region in the 21st century, based on calculation of the relevant climate indices. The projections of the temperature and precipitation characteristics in the Antarctic Peninsula region and Akademik Vernadsky station area for RCP4.5 and RCP8.5 scenarios are the objects of the research.